Jewish-Muslim Intellectual History Entangled Textual Materials from the Firkovitch Collection, Saint Petersburg - Adang, Camilla; Chiesa, Bruno; Hamdan, Omar; Madelung, Wilferd; Schmidtke, Sabine; Thiele, Jan (Cambridge Semitic Languages and Cultures Series, 2020)
"Jewish-Muslim Intellectual History Entangled unearths forgotten texts that once belonged to the library of the Karaite community in Cairo. Consigned to oblivion for centuries, many of these manuscripts were sold in the second half of the nineteenth century to the National Library of Russia in St Petersburg, where they remained inaccessible to most scholars until the end of the Cold War. The texts from the Karaite library cover a remarkable spectrum of medieval literary genres and scholarly disciplines, spanning works by Jewish, Muslim and Christian authors, in both Hebrew and Arabic. As such, they provide unique access to an otherwise lost body of literature from the medieval Islamicate world. This timely volume presents, for the first time, edited fragments of six texts by adherents of the Muʿtazila, a school of rational theology that emerged in the eighth century CE, including Karaite copies and recensions of works by Muslim authors, notably ʿAbd al-Jabbār al-Hamadhānī and ʿAbd Allāh b. Saʿīd al-Labbād, as well as original Jewish Muʿtazilī treatises. The collection is concluded by an anonymous Rabbanite refutation of the highly influential polemical tract against Judaism, entitled Ifḥām al-yāhūd. Is collection offers unprecedented insights into the intellectual crossroads between Muslims and Jews of the Eastern Mediterranean and the Middle East. It will be an invaluable resource to students and scholars engaged with this period of history."